Effect of connectivity and terminal functionality on mesophase behaviour of thermotropic liquid crystals containing biphenyl units - Ranganathan, T.; Ramesh, C.; Kumar, Anil (Liquid Crystals, 2005)
A series of 4,4'-disubstituted biphenyls, designated as series HBC, in which, one substituent is an ester group linked directly to the ring and the other is the hydroxy-containing group O(CH2)(n)OH, have been prepared and analysed by differential scanning Calorimetry, polarizing optical microscopy and X-ray diffraction. The introduction of a trimethylene unit between the ester functional group and the biphenyl moiety of the HBC series gives rise to the HBB series, which did not exhibit liquid crystalline behaviour. Interestingly, mesophase behaviour could be restored by replacing the methylene group ( of the trimethylene unit) that was directly attached to the biphenyl ring by a keto group (HBOB series). When the terminal hydroxy group of these three series was substituted by a group such as acetoxy or hydrogen, the transition temperatures were reduced, and the disappearance of mesophase behaviour was observed in some cases. However, this could be recovered by the replacement of the ester group by a carboxylic acid group.

Main chain thermotropic liquid crystalline polyurethanes containing biphenyl mesogens based on novel AB-type self-polycondensation route: FT-IR and XRD studies - Ranganathan, T.; Gowd, E. B.; Ramesh, C.; Kumar, Anil (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
The detailed mesophasic characterization of main chain liquid crystalline polyurethanes containing biphenyl mesogen, which were synthesized by the novel AB-type self-polycondensation approach, was carried out by using Differential Scanning Calorimetry (DSC), Polarized Optical Microscopy (POM), variable temperature X-ray Diffraction (XRD), and Fourier Transform Infrared (FT-IR) spectroscopic studies. The type of mesophase present in these polymers was identified to be the smectic A phase by POM and XRD studies. The smectic layer thickness was found to increase as the length of the spacer increased. The effect of temperature on the hydrogen bonding was analyzed by FT-IR studies. The curve-fitting analysis of the NH stretching and C=O stretching modes of vibrations indicated a gradual decrease in hydrogen bonding during the transition from the crystalline state to the mesophase. The mesophase to isotropic liquid transition was then accompanied by the complete disappearance of the hydrogen bonding. The biphenyl bands also showed changes during phase transitions due to the coupling of biphenyl vibration modes with the urethane linkage attached to it. (c) 2005 Wiley Periodicals, Inc.
Keywords: FT-IR; liquid-crystalline polymers; polyurethanes; XRD studies

Synthesis and characterization of main chain thermotropic liquid crystalline polyesters based on methyl 4-[4 `-(omega-hydroxyalkoxy)blphenyl-4-yl]-4-oxobutyrate: Effects of keto group and connectivity on mesophasic characteristics of biphenyl based AB-typ - Ranganathan, T.; Ramesh, C. (Reactive & Functional Polymers, 2006)
A series of biphenyl based main chain thermotropic liquid crystalline polyesters, poly(hydroxyalkoxybiphenyl oxobutyrate) [PRBOB-2,n (n = 2-8)], containing various methylene spacers was synthesized by using the novel AB-type self-polycondensation route from the monomers, methyl 4-[4'-(omega-hydroxyalkoxy)biphenyl-4-yl]-4-oxobutyrate (HBOB-2,n). The mesophase characteristics of these polyesters was studied using DSC, polarized light optical microscopy and XRD techniques. The transition temperatures were found to decrease upon increasing the spacer length with an even polymer exhibiting higher transition temperature than the odd counterpart. The mesophase type also indicated an odd-even oscillation with the even members showing normal smectic phase and odd members exhibiting tilted smectic phase. The comparison of mesophasic characteristics of these polyesters with that of structurally similar AB-type polyesters indicated that the total number of atoms connecting the mesogen in a polymeric repeat unit governs the nature of the mesophase while the rigidity of the system dictates the magnitude of transition temperatures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AB approach; biphenyl mesogen; effect of connectivity; Liquid crystalline polyesters